Implementation of Loose Part Learning Media to Improve Creativity of Early Children in Sumberjaya Village - Meilasari, Devi; Fauziah, Arifah (Proceeding International Conference on Religion, Science and Education, 2024)
This study aims to describe and examine more deeply the application of loose part learning media to increase the creativity of early childhood in Sumberjaya Village. This type of research is qualitative with a qualitative descriptive approach. The subjects in this study were ten children in the village of Sumberjaya. The process of data analysis is carried out continuously in collecting data that has been obtained from data sources such as observations, interviews and documentation during the research and then analyzed. Data analysis starts from data collection, data reduction, data presentation, and drawing conclusions. The results showed that the Loose part learning media was very good and effective for increasing the creativity of early childhood. Through loose part learning, it can stimulate the ability of early childhood, they can imagine and form an object according to their imagination. It can be seen from the work of loose part materials in the surrounding environment made by children in the form of hats from jackfruit leaves, woven from banana leaves, making various kinds of creations from sand, making airplanes and ships from unused book paper. Children are very happy and enthusiastic in playing with various objects found in the surrounding environment (loose part). Children are able to be creative by using loose part so that they are able to develop creativity in early childhood.